Endoscopic naso-gallbladder drainage versus gallbladder stenting before cholecystectomy in patients with acute cholecystitis and a high suspicion of choledocholithiasis: a prospective randomised preliminary study. (2nd April 2016) - Yang, Min Jae; Yoo, Byung Moo; Kim, Jin Hong; Hwang, Jae Chul; Baek, Nam Hyun; Kim, Soon Sun; Lim, Sun Gyo; Kim, Ji Hun; Shin, Sung Jae; Cheong, Jae Youn; Lee, Kee Myung; Lee, Kwang Jae; et al.
Abstract: Objective Endoscopic transpapillary gallbladder drainage using a nasocystic tube or plastic stent has been attempted as an alternative to percutaneous drainage for patients with acute cholecystitis who are not candidates for urgent cholecystectomy. We aimed to assess the efficacy of single-step endoscopic drainage of the common bile duct and gallbladder, and to evaluate which endoscopic transpapillary gallbladder drainage method is ideal as a bridge before elective cholecystectomy.Materials and methods From July 2011 to December 2014, 35 patients with acute moderate-to-severe cholecystitis and a suspicion of choledocholithiasis were randomly assigned to the endoscopic naso-gallbladder drainage (ENGBD) ( n  = 17) or endoscopic gallbladder stenting (EGBS) ( n  = 18) group.Results Bile duct clearance was performed successfully in all cases. No significant differences were found between the ENGBD and EGBS groups in the technical success rates [82.4% (14/17) vs. 88.9% (16/18), p  = 0.658] and clinical success rates [by intention-to-treat analysis: 70.6% (12/17) vs. 83.3% (15/18), p  = 0.443; by per protocol analysis of technically feasible cases: 85.7% (12/14) vs. 93.8% (15/16), p  = 0.586]. Three ENGBD patients and two EGBS patients experienced adverse events ( p  = 0.658). No significant differences were found in operation time or rate of conversion to open cholecystectomy.Conclusions Single-step endoscopic transpapillary drainage of the common bile duct and gallbladder seems to be an acceptable therapeutic modality in patients with acute cholecystitis and a suspicion of choledocholithiasis. There were no significant differences in the technical and clinical outcomes between ENGBD and EGBS as a bridge before cholecystectomy.